Precautions against cross-infection during operations for maxillofacial trauma - N. Pigadas,* C. M. E. Avery (Blackwell Synergy, 2000)
Avoiding exposure to contamination by potentially infectious body fluids remains an important principle in the prevention of disease transmission. Barrier methods are particularly important for protection against hepatitis C and the human immunodeficiency virus (HIV) as there is no vaccine or immunoglobulin treatment currently available.